Hubungan Dukungan Keluarga Dengan Tingkat Depresi Pada Ibu Postpartum Di Poliklinik Obsgyn Rumah Sakit Umum DaerahDr. Moewardi - Wijaya, Budi Andri; , Arum Pratiwi, S.Kp., M.Kes (2017)
Mothers who experience depression postpartum will usually feel anxious, sad, can not rest, and some are accompanied by feelings of guilt, lack of energy, motivation and feeling useless. Some women even feel worried and hurt themselves and their babies. The main factors affecting depression postpartum is social support given by her husband and family. The risk of depression will be higher if the mother who gave birth to no support from the husband or the father of the baby. This study aims to determine the relationship of family support to the level of depressionpostpartum motherin Polyclinic Obsgyn Hospital Dr. Moewardi. This type of research is quantitative. The study design was descriptive correlative with approach cross sectional.The research was conducted in Polyclinic Obsgyn Hospital Dr. Moewardi on 15 April to 10 May 2017. The samples used as many as 57 respondents taken by quota sampling. Data collection techniques using questionnaires and data analysis used was correlation Spearman rank test. Based on the results of the study showed that the Correlation test Spearman Rank obtained by value rs of -0.571 with a significance value (p-value) of 0.000. P-value less than 0.05 then the decision is a test of H0 is rejected, so that concluded there is a significant relationship between family support with the level of maternal depression postpartum in Polyclinic Obsgyn Regional General Hospital Dr. Moewardi.